From Dreamer to Player: Improve Entrepreneurial Mindset Student - Frida Zakiya Harasuna; Alfiesyahrianta Habibie; Aulia Suhesty; Suhardiman Suhardiman; M. Ibnu Ashari. R (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2026)
Educated unemployment, which remains high in Indonesia, requires universities to produce job-seeking graduates and job creators through entrepreneurship development. However, students’ interest in entrepreneurship is often not matched by adequate readiness of mindset. This study aims to analyze the effectiveness of role model–based entrepreneurship seminars in shaping the entrepreneurial mindset of new members of the Student Entrepreneur Community (SEC) at the Faculty of Social and Political Sciences, Universitas Mulawarman. The implementation methods included initial assessment, group formation, core training by real business practitioners, direct mentoring for business idea presentations, and cognitive evaluation through pre- and post-tests using a standardized questionnaire analyzed with the t-test. The results showed a significant increase in entrepreneurial mindset scores (p=0.040), accompanied by a shift in participants’ mindset from passive to more active, willing to take risks, and confident in starting a business. Soft skills, such as tolerance for uncertainty and action orientation, increased, while hard skills in drafting simple business plans were also honed. Participant evaluation of the role model showed a very high satisfaction rate (90–98%). Role model–based entrepreneurship workshops were effective in shaping students’ entrepreneurial mindset. Longitudinal studies and the development of psychological capital are recommended for future research.Pengangguran terdidik, yang tetap tinggi di Indonesia, menuntut perguruan tinggi untuk menghasilkan lulusan pencari kerja dan pencipta lapangan kerja melalui pengembangan kewirausahaan. Namun, minat mahasiswa terhadap kewirausahaan sering kali tidak diimbangi dengan kesiapan pola pikir yang memadai. Studi ini bertujuan untuk menganalisis efektivitas seminar kewirausahaan berbasis role model dalam membentuk pola pikir kewirausahaan anggota baru Student Entrepreneur Community (SEC) di Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman. Metode pelaksanaan meliputi asesmen awal, pembentukan kelompok, pelatihan inti oleh praktisi bisnis nyata, pendampingan langsung untuk presentasi ide bisnis, serta evaluasi kognitif melalui pre-test dan post-test menggunakan kuesioner standar yang dianalisis dengan t-test. Hasil penelitian menunjukkan adanya peningkatan signifikan skor pola pikir kewirausahaan (p=0,040), disertai dengan pergeseran pola pikir peserta dari pasif menjadi lebih aktif, berani mengambil risiko, dan percaya diri untuk memulai usaha. Keterampilan lunak, seperti toleransi terhadap ketidakpastian dan orientasi tindakan, meningkat, sedangkan keterampilan keras dalam merancang rencana bisnis sederhana juga terasah. Evaluasi peserta terhadap role model menunjukkan tingkat kepuasan yang sangat tinggi (90–98%). Workshop kewirausahaan berbasis role model efektif dalam membentuk pola pikir kewirausahaan mahasiswa. Studi longitudinal dan pengembangan modal psikologis direkomendasikan untuk penelitian selanjutnya.